An Enhancement of the Solar Panel Efficiency: A Comprehensive Review - Parthiban, R.; Ponnambalam, P. (Frontiers in Energy Research, 2022)
Recently solar panels are gaining popularity in the field of non-conventional energy sources for generating green and clean electric power. On the negative side, the photovoltaic efficiency is reduced with an increase in ambient temperature. The production of energy is dropped by 0.33% for every degree Celsius above STC. Consequently, the electric power which is generated by the solar panel may not be sufficient to run the load. It is important to realize that in some applications, such as standalone electric vehicles, space for providing an additional solar panel to compensate for the decremented output power may not be feasible. By implementing the cooling arrangements, this excessive heat might be reduced. Several cooling techniques have been implemented, named as active and passive methods. This article presents a review on maximizing the efficiency of the solar panel by utilizing different cooling methods and by integrating TEG with solar panels.